2010
DOI: 10.1118/1.3416924
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of polycrystalline photoconductors for radiation therapy imaging

Abstract: Purpose: Electronic portal imaging devices based on megavoltage ͑MV͒, active matrix, flat-panel imagers ͑AMFPIs͒ are presently regarded as the gold standard in portal imaging for external beam radiation therapy. These devices, employing indirect detection of incident radiation by means of a metal plate plus phosphor screen combination, offer a quantum efficiency of only ϳ2% at 6 MV, leading to a detective quantum efficiency ͑DQE͒ of only ϳ1%. In order to significantly improve the DQE performance of MV AMFPIs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Therefore, when all of the MLI layers are combined, the total efficiency is five times that of the AS1200. A more complete presentation of the imaging performance characteristics of the MLI and comparison with the AS1200 can be found in Rottmann et al 8 The signal and noise performance of an indirect imaging system (such as the MLI) can be fully characterized in terms of MTF, NPS, and DQE. 37 The Swank factor was implied in the measurement and calculation of NPS and DQE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when all of the MLI layers are combined, the total efficiency is five times that of the AS1200. A more complete presentation of the imaging performance characteristics of the MLI and comparison with the AS1200 can be found in Rottmann et al 8 The signal and noise performance of an indirect imaging system (such as the MLI) can be fully characterized in terms of MTF, NPS, and DQE. 37 The Swank factor was implied in the measurement and calculation of NPS and DQE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts to improve EPID imaging performance characteristics have mainly focused on replacing the phosphor material with segmented crystalline scintillators, [3][4][5][6] exploiting Cerenkov radiation 7 or employing direct detection methods. 8 Such studies often demonstrate very high DQE; for example, Star-Lack et al 5 reported a DQE approximately 25 times higher than that of a conventional EPID. The main drawbacks are the cost and complexity of manufacturing and implementation, which can be challenging obstacles to clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…The later can be improved by developing a PbO blocking structure, as it was successfully done for a-Se 16 . However, HgI 2 layers are toxic in the sense that they chemically react with imaging array electronics, thus creating additional technological challenges 39 , 40 . Currently, the major competitors of PbO seems to be perovskite photoconductors, for example methylammonium lead iodide (CH 3 NH 3 PbI 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, AMFPI prototypes employing ~210 to 635 μm of polycrystalline HgI 2 material prepared using both the PVD and PIB methods have been examined under radiographic, fluoroscopic and radiotherapy imaging conditions. (Du et al , 2008; Zhao et al , 2010; Zentai et al , 2004) In addition, an early investigation of the performance of an AMFPI prototype coated with 240 μm of PVD HgI 2 under mammographic imaging conditions demonstrated DQE values up to ~60%. (El-Mohri et al , 2003) However, the performance of prototype imagers incorporating PIB HgI 2 has not been previously investigated for mammographic imaging.…”
Section: Introductionmentioning
confidence: 99%